Application of Minimalist Modern Concept in Bed and Family Rooms in Swiss-Bel Hotel, Nusa Dua Badung-Bali - Prastiawan, I Made Dwi; Wiryawan, I Wayan (Journal of A Sustainable Global South; Vol 2 No 2 (2018): August 2018, 2018)
In a hotel building a bedroom is the main facility that becomes the most important unit in a hotel building. In the design of the interior contained in the bedroom and living room owned by the Swiss-Bel hotel located in South Kuta District - Badung Regency using the application of the Modern Minimalist concept that can give the impression of luxury and simplicity in a design that is applied to the constituent elements such as material , furniture and colors used by the room so as to provide a maximum comfortable and peaceful atmosphere for guests who use it and display a strong modern minimalist concept in the room. Index Terms — interior design, modern minimalist concept, bedroom, living room.